Criminal Law Enforcement Against Land Grabbers in the Jambi Regional Police Jurisdiction - Muhamad Mujib; Achmad Arifulloh (UNISSULA Semarang, 2025)
Abstract. Based on the provisions of the 1945 Constitution, Law Number 5 of 1960 concerning Basic Agrarian Regulations was drafted. One of the objectives of the Basic Agrarian Law (UUPA) is to provide legal certainty regarding land rights held by the community. An individual or legal entity wishing to have their land ownership officially recognized by the state and their rights guaranteed must register the land to obtain written proof, in the form of a land certificate. A land certificate can be obtained through land registration. Land registration can help determine the status, ownership, rights, area, and use of the land. According to Santoso, proof of land rights is indicated by the existence of a certificate. In reality, the land registration process is still far from perfect. In Indonesia, only about 44 million plots of land have been registered out of approximately 125 million plots of land, calculated from the emergence of the UUPA until 2016. Then in 2017, the Complete Systematic Land Registration Program (PTSL) was formed by the Ministry of ATR/BPN with a target of certifying 126 million plots of land by 2025 in Indonesia. Land certificates serve as a guarantee of legal certainty, as long as no other party can deny it. In general, besides certificates, there are other formal documents that function as documents of land ownership rights, namely ownership deeds. In the negative land registration system, the formal document is referred to as a